2012
DOI: 10.1108/14720701211214052
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and environmental reporting: an Australian study

Abstract: Purpose -The purpose of this paper is to investigate the relationship between environmental reporting and corporate governance attributes of companies in Australia.Design/methodology/approach -The paper adopts a quantitative analysis approach. It examines the 2008 annual reports of the largest 100 Australian firms listed on the Australian Stock Exchange (ASX) to determine the amount of environmental reporting -these data are compared with various corporate governance measures.Findings -Analysis found a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
151
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(174 citation statements)
references
References 58 publications
(128 reference statements)
15
151
3
5
Order By: Relevance
“…With regard to the effect of board size on the level of sustainability disclosure, some recent studies have found a significant positive relationship between board size and the level of sustainability disclosure (e.g., Rao et al 2012;Said et al 2009). This study follows these findings and develops a tentative proposition namely: P1.…”
Section: Conceptual Discussion and Research Propositionsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the effect of board size on the level of sustainability disclosure, some recent studies have found a significant positive relationship between board size and the level of sustainability disclosure (e.g., Rao et al 2012;Said et al 2009). This study follows these findings and develops a tentative proposition namely: P1.…”
Section: Conceptual Discussion and Research Propositionsmentioning
confidence: 99%
“…Many studies on corporate governance in relation to sustainability issues have considered the role of the board in the form of size, diversity and independence (e.g., AlShammari and Al-Sultan 2010; Barros, Boubaker and Hamrouni 2013;Rao et al, 2012;Rupley, Brown and Marshall 2012;Samaha et al 2012;Said, Zainuddin and Haron 2009).…”
Section: Conceptual Discussion and Research Propositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…One highly debated characteristic of board diversity is gender (Rao, Tilt, & Lester, 2012). The representation of women on boards is generally very low worldwide, including in developed economies; for example, women represent 12.4% of board members in the United States, 6.4% in the United Kingdom, and less than 5% in Canada (Javed, Saeed, Lodhi, & Malik, 2013).…”
Section: Board Diversitymentioning
confidence: 99%
“…Related studies indicate that industry competition could exert external governance effects by constraining manager behavior [66]. In addition, the condition of corporate governance has a significant impact on the level of CSR information disclosure [67,68]. A recent study of Chinese listed firms found that firms in low monopoly industries are more likely to disclose CSR reports [69].…”
Section: Control Variablesmentioning
confidence: 99%